599 Bullying and Harassment Awareness Amongst Junior Doctors – an Audit in Morriston Hospital Plastic Surgery Department. (19th August 2022) - Hadjikyriacou, E; Mistry, R
Abstract: Aim: Determine junior doctors' awareness of bullying and harassment policy and legal requirements of the health board. If lack of knowledge/training, provide required training in the form of staff teaching. Improve workplace culture and staff safety. Method: All junior doctors (total of 10) in the plastic surgery department were asked to fill in questionnaire about their experience of bullying and harassment in the workplace. They were asked about their personal experience of bullying and harassment, awareness of the health boards duty, reporting culture and barriers to reporting. The change implemented was staff training and information on where to access health board policies and protocols. After training, a second questionnaire was filled in to see if there was better understanding of the health board policy and the necessary steps in the event of a bullying or harassment incident. Results: The health boards policy was easy find on the health board intranet. In the initial questionnaire: 6 out of 10 junior doctors reported experiencing bullying or harassment in the NHS, all 10 reported not being able to define bullying and harassment; and a lack awareness of NHS Wales' bullying and harassment policy. All 10 reported that they had not reported any bullying and harassment experienced. The junior doctors were asked about barriers to reporting, all 10 identified concerns about repercussions professionally as the main barrier. Conclusions: Training on how to identify bullying and harassment, the pathways of escalation and a change in culture over professional repercussions are vital for surgical trainees going forward in the NHS.